Temperature-Regulated IncX3 Plasmid Characteristics and the Role of Plasmid-Encoded H-NS in Thermoregulation - Baomo, Liu; Lili, Shui; Moran, Robert A.; van Schaik, Willem; Chao, Zhuo (Frontiers in Microbiology, 2022)
Carbapenem-resistant Enterobacteriaceae (CRE) are a critical public health problem worldwide. Globally, IncX3-type plasmids have emerged as the predominant vehicles carrying the metallo-β-lactamase gene blaNDM. Although blaNDM-bearing IncX3 plasmids have been found in various hosts from diverse environments, whether their transfer and persistence properties vary under different conditions and what factors influence any variation is unknown. By observing the effects of different temperatures on IncX3 plasmid conjugation rates, stability and effects on host fitness in E. coli, we demonstrate that temperature is an important determinant of plasmid phenotypes. The IncX3 plasmid pGZIncX3 transferred at highest frequencies, was most stable and imposed lower fitness costs at 37°C than at other temperatures. Temperature-regulated variation in pGZIncX3 properties involved a thermoregulated plasmid-encoded H-NS-like protein, which was produced at higher levels at 30°C and 42°C and inhibited the expression of type IV secretion system genes involved in conjugation. These findings suggest that blaNDM-bearing IncX3 plasmids are adapted to carriage by enterobacteria that colonize mammalian hosts and could explain the rapid dissemination of these plasmids among human-associated species, particularly in hospital settings.